The mathematics in the journal The Little Lutheran in the 1950s - Malcus Cassiano Kuhn; Arno Bayer (Universidade Federal de Santa Catarina, 2018)
The Missouri Synod, nowadays Evangelical Lutheran Church of Brazil, started mission in the German colonies of Rio Grande do Sul, in 1900, founding religious congregations and parochial schools. These were inserted in a missionary and community project that sought to teach the mother tongue, mathematics, and cultural, social, and mainly religious values. In this context, the Lutheran Church edited the journal The Little Lutheran for the infantile public, in the period from 1939 to 1966. The main objective of the journal's editors was, in a playful way, insert the children in the Lutheran religious practice through  stories, information and curiosities of moral and religious nature and general education. It was used, complementarily, in the teaching of the different areas of knowledge in the gaucho Lutheran parochial schools of the past century. This article aims to discuss the mathematics present in the journal The Little Lutheran in the 1950s. Being based on the methodological approach of the historical research and of the cultural history, the editions of the journal, written by Lutheran pastors and parochial teachers were analyzed  and published by Concordia Publishing House of Porto Alegre. It was found that the journal editors have integrated the moral and religious nature stories with mathematics, with the purpose of maintaning the children inserted in the Lutheran religious practice.  Curiosities  and mathematical challenges were also presented  that valued the concrete and abstract skills of the mathematical learning through  the logical reasoning, of the proportional thought, of the written calculation and of the mental calculation, in form of playful activities.